Palladium‐Catalyzed Rapid Methoxylation and Deuteriomethoxylation of Bromo–chalcones: Uncovering the Catalytic Activity of the Pd/tBuXPhos Catalyst System. Issue 21 (23rd December 2016) - Reeta; Rangarajan, T. M.; Ayushee; Singh, Rishi Pal; Singh, R. P.
Abstract: We report an unprecedented t BuXPhos ligand (L3 ) supported Pd‐catalyzed rapid methoxylation and deuteriomethoxylation of bromo‐chalcones (5 to 40 min.) with excellent yields. Pd/RockPhos (L2 ) catalytic system also facilitates the coupling reaction, but the reaction time is fairly longer than Pd/ t BuXPhos (L3 ) catalytic system. The coupling of MeOH/MeOH‐ d4 with 4‐bromo‐chalcones is so rapid than that of 3‐bromo‐chalcones, which clearly indicates that the former proceeds through a pure electronic pathway of reductive elimination. These catalyst systems facilitate the coupling of 4‐bromo‐chalcones even with higher alkyl alcohols relatively long reaction time that implies the efficiency and rate of coupling relays on the nucleophilicity of the alcohols. This methodology may be adopted for the 11 C‐radiolabeling of organic compounds for PET imaging applications. Abstract : t BuXPhos ligand is found to be a most effective (highly active and relatively inexpensive) Buchwald type ligands in Pd‐catalyzed rapid methoxylation and deuteriomethoxylation of bromo‐chalcones. Most of the bromo‐chalcones coupled with methanol/methanol‐ d4 in short reaction times (about 5 min.). This catalyst system demonstrated methanol is not to be a week nucleophile in Pd‐catalyzed C−O cross‐coupling reaction. This methodology may be adopted for the 11 C‐radiolabeling of bromo‐chalcones for PET imaging applications.